Situation Report: Romania, 5 October 1984 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Romanian Economists Criticize Extensive Growth Model / by Anneli Maier; Dan Ionescu Is the Party Losing Its Authority? / by Paul Gafton The Danube-Black Sea Canal: Anatomy of a White Elephant / by Vladimir Socor